2020
DOI: 10.26719/emhj.19.094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and anti-hepatitis C virus antibody among people who inject drugs in the Lebanese population

Abstract: Background: People who inject drugs (PWIDs) are prone to a number of blood-borne viral infections. Hepatitis B virus (HBV) and hepatitis C virus (HCV) constitute an important public health concern in this high risk group. Aims: We aimed to determine the prevalence of HBV and HCV antibody among PWIDs in Lebanon. Methods: We conducted a prospective cross-sectional study between June 2015 and June 2016 on PWIDs recruited through Lebanese nongovernmental organizations in collaboration with the Lebanese Ministry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Intravenous drug use and blood transfusion are the most common routes of transmission, followed by hemodialysis [ 23 , 27 ]. Vertical and sexual transmissions are the least common routes of infection, representing 0.2% and 0.3% of HCV transmission cases, respectively ( Table 2 ) [ 28 ]. Several studies have reported HCV prevalence among people who inject drugs (PWID) and prisoners.…”
Section: Hcv In Lebanonmentioning
confidence: 99%
See 4 more Smart Citations
“…Intravenous drug use and blood transfusion are the most common routes of transmission, followed by hemodialysis [ 23 , 27 ]. Vertical and sexual transmissions are the least common routes of infection, representing 0.2% and 0.3% of HCV transmission cases, respectively ( Table 2 ) [ 28 ]. Several studies have reported HCV prevalence among people who inject drugs (PWID) and prisoners.…”
Section: Hcv In Lebanonmentioning
confidence: 99%
“…Several studies have reported HCV prevalence among people who inject drugs (PWID) and prisoners. In a recent study conducted in 2020, HCV prevalence among 250 PWID was 15.6% [ 28 ], while previous studies showed a higher rate, reaching 52.8% [ 19 ]. In another small study, HCV prevalence among prisoners was 3.4% [ 29 ], with a higher rate of 28.1% reported a few years later in a larger study [ 30 ].…”
Section: Hcv In Lebanonmentioning
confidence: 99%
See 3 more Smart Citations